Tinjauan Komprehensif Tentang Model Kematangan Budaya Keselamatan di Sektor Pertambangan - Muhammad Osaegi Restu Amrulloh; Endik Riyanto (Lembaga Pengembangan Kinerja Dosen, 2024)
Many researchers are interested in evaluating the quality of safety cultures, particularly in the mining industry. Keputusan Dirjen Minerba Nomor 185 Tahun 2019, in Element II of the initial review section, has developed a five-level safety culture maturity assessment framework. This study aims to investigate the conceptualization and foundation of developing safety culture maturity levels in the mining sector and provides an educational overview of the application of the developed model with five cultural maturity levels: basic, reactive, planned, proactive, and resilient. This research employs a systematic review methodology using the literature review method. Databases such as Google Scholar and Science Direct were utilized, focusing on specific keywords: